Comprehensive Analysis of Prognostic Value and Immune Infiltration of Chromobox Family Members in Colorectal Cancer - Li, Qingshang; Pan, Yi; Cao, Zhijun; Zhao, Shuliang (Frontiers in Oncology, 2020)
Objective: Colorectal cancer (CRC) is a common malignant tumor worldwide. Chromobox (CBX) family proteins are important components of epigenetic regulation complexes and are implicated in the development of multiple cancers by blocking differentiation and promoting proliferation. However, little is known about the function of distinct CBX proteins in colorectal cancer. Methods: Oncomine, Gene Expression Profiling Interactive Analysis (GEPIA), Kaplan-Meier plotter, cBioPortal, GeneMANIA, and TIMER were utilized to analyze differential expression, prognostic value, genetic alteration and immune cell infiltration of CBXs in colorectal cancer patients. Results: The expression levels of CBX1/2/3/4/5 and CBX8 were significantly elevated in CRC tissues, whereas the expression levels of CBX6/7 were reduced. CBX3 was significantly associated with the clinical cancer stage and short disease-free survival (DFS) in CRC patients. High mRNA expression of CBX5/6 was associated with short overall survival (OS) in rectal cancer patients. CBX3/5/6 could be potential prognostic biomarkers for the survival of CRC patients. Moreover, the functions of the differentially expressed CBXs were primarily related to the SUMOylation of DNA methylation proteins and chromatin organization and may regulate the pluripotency of stem cells. There were significant correlations among the expression of CXC chemokines and the infiltration of six types of immune cells (B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells). Conclusions: Our study may provide novel insights for the selection of prognostic biomarkers of CBX family in colorectal cancer.